Lateral cephalometric radiograph versus lateral nasopharyngeal radiograph for quantitative evaluation of nasopharyngeal airway space - Pereira,Suelen Cristina da Costa (2014)
OBJECTIVE: This study compared lateral radiographs of the nasopharynx (LN) and lateral cephalometric radiographs (LC) used to assess nasopharyngeal airway space in children. MATERIAL AND METHODS: One examiner measured the nasopharyngeal space of 15 oral breathing patients aged between 5 and 11 years old by using LN and LC. Both assessments were made twice with a 15-day interval in between. Intergroup comparison was performed with t-tests (P < 0.05). RESULTS: Comparison between LN and LC measurements showed no significant differences. CONCLUSION: Lateral cephalometric radiograph is an acceptable method used to assess nasopharyngeal airway space.